1995
DOI: 10.1128/jb.177.19.5440-5446.1995
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Mal61p in Saccharomyces cerevisiae and characterization of maltose transport in artificial membranes

Abstract: For maltose uptake in Saccharomyces cerevisiae, multiple kinetic forms of transport as well as inhibition of transport by high concentrations of maltose at the trans side of the plasma membrane have been described. Most of these studies were hampered by a lack of genetically well-defined mutants and/or the lack of an artificial membrane system to study translocation catalysis in vitro. A genetically well-defined S. cerevisiae strain lacking the various MAL loci was constructed by gene disruption. Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 50 publications
2
33
0
2
Order By: Relevance
“…One effect of external alkalinity is the disruption of membrane proton gradients, which normally supply energy for nutrient and ion transport (10). Prior studies indicated that yeast responds by expressing ENA1, a plasma membrane Na ϩ -ATPase gene (14,18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One effect of external alkalinity is the disruption of membrane proton gradients, which normally supply energy for nutrient and ion transport (10). Prior studies indicated that yeast responds by expressing ENA1, a plasma membrane Na ϩ -ATPase gene (14,18).…”
Section: Discussionmentioning
confidence: 99%
“…4). The rim101⌬ strain grew poorly in the presence of NaCl and LiCl, as do ena1 mutants (10,42). This growth defect did not arise from general osmotic sensitivity because RIM101 and rim101⌬ strains grew equally well on medium 3-6 and 7-10, respectively).…”
Section: Requirement For Rim101p In Alkaline Responsementioning
confidence: 99%
See 2 more Smart Citations
“…This so called trans-inhibition involves a decrease in transport activity as the intracellular substrate concentration increases and has been well-described for bacterial transport systems involved in osmoregulation (Poolman and Glaasker 1998). Studies in hybrid membranes with overexpressed Mal61p indicate that maltose transport is reversible, because influx as well as efflux transport can be observed (Van der Rest et al 1995). Since the orientation of the maltose transporter in the hybrid membranes is most likely random, these experiments do not rule out the possibility that the maltose transport system is trans-inhibited or, for some other reason, kinetically different for uptake and efflux transport, as both modes of transport may be facilitated by oppositely oriented Mal61p molecules.…”
Section: Introductionmentioning
confidence: 99%